2018
DOI: 10.1155/2018/5684261
|View full text |Cite|
|
Sign up to set email alerts
|

Production of Biosurfactants by Soil Fungi Isolated from the Amazon Forest

Abstract: Biosurfactants are surface-active compounds that have sparked interest in recent years because of their environmental advantages over conventional surfactants. The aim of this study was to investigate the production of biosurfactants by soil fungi isolated from the Amazon forest. Fungi colonies were isolated from soil samples and screened for biosurfactant production in submerged fermentation. In addition, the influences of bioprocess factors (carbon source, nitrogen source, pH, and fermentation time) were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 31 publications
1
14
1
1
Order By: Relevance
“…The authors who focused on the analysis of any fungal biosurfactants applied similar analytical methods to those presented in this work, as well as the procedure for metabolite separation. The drop-collapse method appears to be the simplest, however the results obtained are not only often misleading, but also dependent on the duration of the analysis [ 1 , 9 , 15 , 22 ]. Another simple and reasonably fast method is surface tension assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors who focused on the analysis of any fungal biosurfactants applied similar analytical methods to those presented in this work, as well as the procedure for metabolite separation. The drop-collapse method appears to be the simplest, however the results obtained are not only often misleading, but also dependent on the duration of the analysis [ 1 , 9 , 15 , 22 ]. Another simple and reasonably fast method is surface tension assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the carbon source, glucose and sucrose were as a rule used in the production of biosurfactants. Sena et al [ 9 ] evaluated the secretion of biosurfactants in different strains of fungi throughout different sources of carbon and nitrogen, at a concentration of 20 g/L and 10g/L, respectively, as well as soybean oil, sucrose, cellobiose, xylose, yeast, meat, and malt extract. The authors did not use the mineral solution for their tests, and the results for Trichoderma strains did not encourage them to further study them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these dominant fungi are characterized by their genomic potential for use in biotechnological resources, competition International Journal of Microbiology between microorganisms in the environment, and stress tolerance compared to other fungi; however, studies suggest that ascomycetes may be better equipped to withstand environmental stresses and can utilize a higher number of resources, thus leading to more generalist strategies that may contribute to their increased dominance in soils. Aspergillus, Penicillium, and Fusarium, among others, are ascomycetes that are being studied as biosurfactant producers [41][42][43]. Table 1 provides an overview of a few sources of isolation and types of reported biosurfactants produced by these ascomycetes.…”
Section: Biosurfactant Production By Ascomycetesmentioning
confidence: 99%
“…Increasing evidence revealed that the success of filamentous fungi in mycoremediation is aided by their ability to make pollutants more bioavailable, through the production of biosurfactants [ 7 , 8 ]. However, only a few studies have revealed the presence of biosurfactant-producing Trichoderma strains [ 9 , 10 ]. The production of bioactive compounds by a fungal strain is another important parameter when assessing mycoremediation potential: it redirects nutrient flux from decomposed wastes into molecules that are beneficial to the fungus, guaranteeing competitiveness of the strain and promoting co-metabolization of chemicals, but it also represents a drawback in terms of safety application [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%